The STUDENTS’ MENTAL MODEL ABOUT NEWTON’S THIRD LAW IN INDONESIA - Cahya Dinata, Pri Ariadi; Rahzianta, Rahzianta; Suparwoto, Suparwoto (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The effective learning can be built by comprehend the students’ prior knowledge. However, it is rare for teacher to arrange learning based on students’ alternative concepts, particularly be related to force and motion concept. Based on those problems, this research is aims to describe student’s mental model about Newton’s Third Law. The methods is testing by four essay items about to action-reaction forces. Those items asked students to explain, predict, and evaluate the phenomenon which is related to Newton’s Third Law. The sample include 140 students from 3 provinces in Indonesia, that consist of D.I Yogyakarta, South Borneo, and West Borneo. The results showed that there is many students held diverge mental model about action-reaction forces. The divergences among others are: the greater the mass, the greater the force in collision phenomenon; the resting object can’t exert reaction force; the action-reaction forces can be cancelling each other. The suggestion to overcome those mental models is discussed. We hope these result can be applied by others teachers to construct better leaning about Newton’s Third Law.